The Role of the Core Banking System: The Case of Bank Aceh’s Syariah Conversion - Deni Amin Sujana; Mukhlisin, Murniati (Muslim Business and Economics Review, 2024)
The aim of this study is to assess the transformation of a traditional banking system into an Islamic banking system. Utilizing a case study approach and drawing on asset-liability theories, Bank Aceh is chosen for examination of both pre- and post-conversion. The results indicate that the implementation of Qanun (Islamic law) expedited the conversion process in Aceh, by mandating that financial institutions in the province operate under Islamic principles. A unique aspect of this research is the exploration of the conversion process from an information technology perspective, specifically examining the role of the core banking system in transitioning from conventional to Islamic banking. Additionally, the study sheds light on the accounting treatment within the core banking system during the conversion process, a previously unexplored aspect.